REPORT OF THE COMMITTEE ON DOCTORAL PROGRAMS IN ACCOUNTING. - Anthony, Robert N.; Ashburne, Jim G.; Bastable, Charles W.; Dunn, Clarence L.; Fertig, Paul E.; Nielsen, Oswald; Schlatter, William J.; Bedfrod, Norton M. (The Accounting Review, 1961)
Abstract This article presents the report of the Committee on Doctoral Programs in Accounting. The committee made various recommendations on how to improve the Doctoral programs. It suggested that the doctoral program is the principal educational process for preparing students both for university teaching and for basic research in accounting. Hence the primary objective of the study program for the doctorate should be to develop in the student original and incisive thinking and to create an attitude conducive to study and research. As wide variations in the backgrounds of doctoral students call for individually designed programs of course work, instruction in methods of teaching and familiarity with the learning process should be a part of the doctoral program. At the end of the study program the doctoral candidate should demonstrate proficiency in accounting and a reasonable understanding of economics, statistics, the functional areas of business, the behavioral sciences, and mathematical methods. And finally the demand for college teachers of accounting should not be an excuse for lowering the standards for the doctoral program.